The effectiveness of a dentifrice without sodium lauryl sulphate on dental plaque and gingivitis – a randomized controlled clinical trial. Issue 3 (8th February 2016) - Sälzer, S; Rosema, NAM; Hennequin‐Hoenderdos, NL; Slot, DE; Timmer, C; Dörfer, CE; Van der Weijden, GA
Abstract: Objectives: The purpose of the study was to evaluate the effect on dental plaque and gingivitis of a dentifrice without sodium lauryl sulphate (SLS) compared to two SLS‐containing dentifrices. Material and methods: For this double‐blind, parallel study, 90 volunteers having moderate gingival inflammation (≥40%) were randomly divided among three groups: one group using non‐SLS dentifrice containing enzymes, colostrum and low concentrations of zinc and two control groups each using different SLS‐containing dentifrices. Dental plaque scores (Turesky modification of Quigley & Hein) and gingivitis scores (Bleeding On Marginal Probing) were assessed at baseline, after 2 and 4 weeks. Results: Eighty‐nine participants provided evaluable data. A slight decrease in gingivitis scores was observed for all groups over 4 weeks, which was statistically significant for the non‐SLS group. Mean values for dental plaque scores did not show major differences over 4 weeks. For both parameters, no significant differences between groups could be observed at any time point. Patient appreciation was in favour of the SLS groups especially regarding the foaming effect. Conclusion: No significant differences could be observed with respect to the effect on plaque and gingivitis between SLS‐containing and SLS‐free dentifrice containing enzymes, colostrum and low concentration zinc. Patients enjoyed the duration of taste and the 'foaming effect' of SLS‐containing dentifrices better.